2014
DOI: 10.1007/s00405-014-3174-4
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between clinical findings and eosinophil/neutrophil ratio in patients with nasal polyps

Abstract: Chronic rhinosinusitis with nasal polyps (CRSwNP) is a frequent disease which can be classified as eosinophilic or neutrophilic based on dominant inflammatory cell type at tissue. The aim of this study was to evaluate the clinical relevance of classifying nasal polyps as eosinophilic or neutrophilic on treatment outcomes. The study was conducted with 40 patients who underwent either surgical or medical treatment with the diagnosis of CRSwNP. The patients were classified into two groups for further assessment u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
25
0
4

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 37 publications
6
25
0
4
Order By: Relevance
“…Our findings were in accordance with the findings of a study that reported that patients with CRSwNP demonstrated systemic eosinophilic inflammation [18]. In conclusion, EOS is a significant factor related to the morbidity of CRSwNP.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Our findings were in accordance with the findings of a study that reported that patients with CRSwNP demonstrated systemic eosinophilic inflammation [18]. In conclusion, EOS is a significant factor related to the morbidity of CRSwNP.…”
Section: Discussionsupporting
confidence: 83%
“…Allergic rhinitis diagnostic criteria [18] include: nasal itching, sneezing, nasal discharge, and nasal obstruction, among other symptoms, and a positive allergen sensitization SPT.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, we can conclude that eosinophils may trigger a more severe form of inflammation in the context of CRSwNP compared to the noneosinophilic inflammatory cells. However, our results showed no significant difference between the ECRSwNP and nECRSwNP groups with respect to the SNOT-20 score, VAS score, endoscopy score, or CT score ( p > 0.05); these findings are consistent with the results of a recently published paper that compared the clinical markers of CRS with disease severity [21,22,23]. …”
Section: Discussionsupporting
confidence: 82%
“…Indeed, our own study has shown that the ratio of CT scores for the ethmoid sinus and maxillary sinus (E/M ratio) based on Lund‐Mackay scores had the highest predictive value for ECRS compared with other clinical parameters . Although these studies clearly demonstrate the benefit and accuracy of CT scan in diagnosis of ECRS, and several studies have demonstrated a close association between ECRS and CRS recurrence, none have directly assessed the association between specific CT scan characteristics and CRSwNP recurrence. Thus, in the present study we investigated the correlations between findings of CT scans and CRSwNP recurrence and found that a cut‐off value of 2.55 for E/M ratio on CT scan had the highest predictive value for CRSwNP recurrence, with a sensitivity of 95.8% and a specificity of 91.1%, suggesting an E/M ratio >2.55 was indicative of the likelihood of CRSwNP recurring, even after adequate surgery and postsurgical management with normative intranasal corticosteroid and up to 2 short courses of antibiotics or systemic corticosteroids.…”
Section: Discussionmentioning
confidence: 93%
“…Furthermore, obtaining the tissue is not convenient in the outpatient clinic. Second, irrespective of whether percentage of tissue eosinophils is employed for the diagnosis of ECRS or prediction for CRS recurrence, the criterion for tissue eosinophilia percentage has been shown to range from 5% to 50%, which makes it difficult to define a reliable measure. From this standpoint, the E/M ratio appears to be superior to tissue eosinophil percentage as a prognostic indicator for CRS recurrence.…”
Section: Discussionmentioning
confidence: 99%